KCTD1 and Scalp-Ear-Nipple ('Finlay–Marks') syndrome may be associated with myopia and Thin basement membrane nephropathy through an effect on the collagen IV α3 and α4 chains. (2nd January 2023) - Wang, Dongmao; Trevillian, Paul; May, Stephen; Diakumis, Peter; Wang, Yanyan; Colville, Deb; Bahlo, Melanie; Greferath, Una; Fletcher, Erica; Young, Barbara; Mack, Heather G.; Savige, Judy
ABSTRACT: Introduction: Scalp-Ear-Nipple syndrome is caused by pathogenic KCTD1 variants and characterised by a scalp defect, prominent ears, and rudimentary breasts. We describe here further clinical associations in the eye and kidney. Methods: Fifteen affected members from two unrelated families with p.(Ala30Glu) or p.(Pro31Leu) in KCTD1 were examined for ocular and renal abnormalities. The relevant proteins were studied in the eye and kidney, and the mutation consequences determined from mouse knockout models. Results: Five males and 10 females with a median age of 40 years (range 1–70) with pathogenic variants p.(Ala30Glu) (n = 12) or p.(Pro31Leu) (n = 3) in KCTD1 were studied. Of the 6 who underwent detailed ophthalmic examination, 5 (83%) had low myopic astigmatism, the mean spherical equivalent of 10 eyes was 2.38D, and one (17%) had hypermetropic astigmatism. One female had a divergent strabismus. Five individuals had renal cysts (5/15, 33%), with renal biopsy in one demonstrating a thinned glomerular basement membrane identical to that seen in Thin basement membrane nephropathy (AD Alport syndrome). In the eye, KCTD1 and its downstream targets, TFAP2, and the collagen IV α3 and α4 chains localised to the cornea and near the retinal amacrine cells. In the kidney, all these proteins except TFAP2 were expressed in the podocytes and distal tubules. TFAP2B and COL4A4 knockout mice also had kidney cysts, and COL4A3 and COL4A4 knockout mice had myopia. Conclusion: Individuals with a pathogenic KCTD1 variant may have low myopic astigmatism and represent a further rare genetic cause for a thinned glomerular basement membrane.